Structural Change, Productivity, and the Shift to Services: The Case of Indonesia - Nabil Rizky Ryandiansyah; Iwan Jaya Azis (Economics and Finance in Indonesia, 2018)
Since Chenery & Syrquin (1975), the pattern of transition from agriculture-heavy economies to industry and then later to services has been central to growth literatures. But recent empirical works have casted doubts on whether developing countries are able to follow the same path. This paper analyzes whether structural change in Indonesia has been productivity-enhancing. This paper finds that structural change from 1998-2014 has not been able to generate impact on economy-wide productivity. This paper also explores possible determinants of the direction of structural change. This paper does not find commodity dependence nor human capital to have clear association with low structural productivity that is observed.